Grain boundary character distribution and cavitation behaviour of superlastic deformation in AA7475 - Chen, Chilong. (2008)
Superlastic forming (SPF) of high strength aluminium alloys such as AA7475 has shown great potential in the aerospace and automobile industry. Unfortunately, Al alloys usually suffer from cavitation during SPF, which will lead to the degradation of the overall properties of the post-SPF materials. This motivated the present work to characterize the microstructure evolution.